Penerapan teori pengulangan (repetisi) dalam oral practicing (kelas percakapan) pemelajar BIPA di Australia - Theya Wulan-Primasari (Badan Pengembangan dan Pembinaan Bahasa, 2023)
Speaking skill is an important skill in learning a language. In learning Indonesian for Foreign Speakers (BIPA), speaking skill is considered difficult to teach because of students’ different language backgrounds. The use of repetition theory is proven to be applicable in Indonesian language learning activities in Australia. The author tries to conduct repetition theory to BIPA students at Mount Erin College. In this research, the method used is case study research with qualitative analysis. This paper aims to describe the use of repetition theory in conversation classes (oral practicing) to BIPA students and to describe the result of conversation between teacher and BIPA students simply. This research is hoped that it will provide benefit for BIPA teachers and BIPA activists in general.